Improving Self-Awareness of Motor Symptoms in Patients With Parkinson’s Disease by Using Mindfulness – A Study Protocol for a Randomized Controlled Trial - Buchwitz, Timo Marcel; Maier, Franziska; Greuel, Andrea; Eggers, Carsten (Frontiers in Psychology, 2020)
Objective: This study aims to increase self-awareness in patients with Parkinson’s disease (PD) using a newly developed mindfulness-based intervention, tailored for the specific needs of PD patients. Its impact on self-awareness and patients’ daily lives is currently being evaluated. Background: Recently, the phenomenon of impaired self-awareness for motor symptoms (ISAm) and some non-motor symptoms has been described in PD. ISAm can negatively influence patients’ daily lives, e.g. by affecting therapy adherence, and is therefore the main focus of this study. The main goal is the development of IPSUM (“Insight into Parkinson’s Disease Symptoms by using Mindfulness”), a PD-specific intervention for increasing patients’ mindfulness and thereby reducing ISAm. Methods: The effectiveness of IPSUM is evaluated by comparison of an intervention group with a waitlist-control group. A pre-post design with an additional eight-week follow-up measurement is applied, resulting in three measurement points: before, directly after and eight weeks after completing the intervention protocol. In total, up to 180 non-depressed PD patients without severe cognitive impairment (non-demented) will be included. The primary outcome is a quantitative score for measuring ISAm. Secondary outcome measures are affective changes, neuropsychological performance and self-awareness of cognition. At pre- and post-measurement an fMRI scan is performed to connect behavioral and neurobiological findings. At post- and follow-up-measurement each patient will take part in a semi-structured interview to explore IPSUM's impact on self-awareness and patients’ everyday lives. Results: The conception of the intervention protocol is finished, the resulting eight-week program is presented in detail. It has successfully been tested in the first group of patients, their feedback so far was quite promising. Recruitment is ongoing and a first interim analysis will be performed once 30 patients have completed IPSUM. Conclusions: For the first time, the intervention protocol of IPSUM has successfully been tested in a group of PD patients. As the study goes on, more quantitative data is collected for statistical analyses to evaluate its effectiveness. More qualitative data is collected to evaluate feasibility and effectiveness. We hope for this intervention to be capable of reducing the patients' ISAm and improving their quality of life on many levels.